Pyrazolopyrimidinones, a novel class of copper-dependent bactericidal antibiotics against multi-drug resistant S. aureus. Issue 4 (11th March 2019) - Crawford, Cameron L.; Dalecki, Alex G.; Narmore, Whitney T.; Hoff, Jessica; Hargett, Audra A.; Renfrow, Matthew B.; Zhang, Man; Kalubowilage, Madumali; Bossmann, Stefan H.; Queern, Stacy L.; Lapi, Suzanne E.; Hunter, Robert N.; et al.
Abstract : Pyrazolopyrimidinones traffic copper into S. aureus, depleting ATP and altering essential ion concentrations, resulting in the death of the bacteria. Abstract : The treatment of methicillin-resistant Staphylococcus aureus (MRSA) infections poses a therapeutic challenge as even last resort drugs become increasingly ineffective. As the demand for antibiotics with novel modes of action is growing, new approaches are needed to probe a greater spectrum of antimicrobial activities for their potential efficacy against drug-resistant pathogens. The use of copper (Cu) by the innate immune system to mount an antimicrobial response against bacterial invaders has created an opportunity to explore a role for Cu in antimicrobial therapy. Here we describe pyrazolopyrimidinones (PZP) as novel copper-dependent inhibitors (CDI) of S. aureus . 5-Benzyl-3-(4-chlorophenyl)-2-methyl-4 H, 7 H -pyrazolo[1, 5- a ]pyrimidin-7-one (PZP-915) showed potent bactericidal properties at sub-micromolar concentrations and activity against clinical MRSA isolates and biofilms cultures. This cupricidal activity is founded on the molecule's ability to coordinate Cu and induce accumulation of Cu ions inside S. aureus cells. We demonstrate that exposure to 915 + Cu led to an almost instantaneous collapse of the membrane potential which was accompanied by a complete depletion of cellular ATP, loss of cell-associated K +, a substantial gain of cell associated Na +, and an inability to control the influx of protons in slightly acidic medium, while the integrity of the cell membrane remained intact. These findings highlight PZP-915 as a novel membrane-directed metalloantibiotic against S. aureus that is likely to target a multiplicity of membrane associated protein functions rather than imposing physical damage to the membrane structure.